Determination of the water footprint in the production of the bulb onion crop under two irrigation systems in Samaca (Colombia) - Cely-Reyes, Germán Eduardo; Camargo-Guerrero, Fabiola del Rosario; Fernández-Pérez, Carlos Julio; Walteros-Torres, Ingrid Yaneth; Serrano-Cely, Pablo Antonio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
The water footprint (WF) is an environmental indicator to quantify the total volume of water required by an agricultural system during its productive cycle, important for decision-making in the management of water resources in relation to its availability, to improve the efficiency in the use of irrigation water (WFblue), the use of rainwater (WFgreen) and the quality of water used (WFgray). This research estimated the water footprint of bulb onion (Allium cepa L.) cultivation under two irrigation systems in the municipality of Samaca (Colombia), using Cropwat, weighing lysimeters, climate information, crop water requirements and physicochemical analysis of soils and water. The calculation of the WF by component in sprinkler irrigation was: (WFblue) 75.65 m3 t-1, (WFgreen) 67.53 m3 t-1 and (WFgray) 31,29 m3 t-1 ; in drip irrigation: (WFblue) 78.72 m3 t-1, (WFgreen) 65.28 m3 t-1 and (WFgray) 52.4 m 3 t-1. WF maintained a similar trend between irrigations: sprinkler (174.47 m3 t-1) with a yield of 56.0 t ha-1 and drip (196.41 m3 t-1) with a yield of 57.9 t ha-1.